Boundaries and hybridization in a secondary contact zone between freshwater mussel species (Family:Unionidae) - Porto-Hannes, Isabel; Burlakova, Lyubov E; Zanatta, David T; Lasker, Howard R (Heredity, 2021)
Correct species identification and delineation are crucial for effective conservation and management. However, species delineation can be problematic in the presence of morphological ambiguities due to phenotypic plasticity, convergence, and/or interspecific hybridization. Here, we investigated the degree of hybridization between two closely related freshwater mussel species [Bivalvia: Unionidae; Lampsilis siliquoidea (Barnes) and L. radiata (Gmelin)] that present intermediate forms in areas of sympatry. Unionids have a distinct form of mitochondrial DNA (mtDNA) inheritance, termed doubly uniparental inheritance (DUI) where female mtDNA (F-type) is transmitted to all progeny but male mtDNA (M-type) is mostly inherited by the males resulting in mostly homoplasmic females and heteroplasmic males. An individual was identified as hybrid when F-type and M-type mtDNA of the two different species were found in the same individual. Twelve out of 116 sequenced males were identified as hybrids indicating that these species hybridize where their geographic range overlaps in the lower Great Lakes and St. Lawrence basins. Microsatellite analyses further support the occurrence of hybridization but at a larger spatial scale than indicated by the mitochondrial analyses. We also found that strong within-species population genetic structure affects the detection of purebred individuals overestimating the number of hybrids. Given the large geographic scale and proportion of hybrids found in this study, natural hybridization and introgression need to be considered when implementing local biodiversity inventories, identifying waterbodies as source of organisms for relocation and restoration projects and when setting appropriate conservation policies.